The Influence of Principal Transformational Leadership on Teacher Performance through Organizational Commitment and Job Satisfaction - Maulida, Ratna Siti; Zohriah, Anis; Hilmiyati, Fitri; Itang, Itang; Nadhirah, Yahdinil Firda (Paedagoria : Jurnal Kajian, Penelitian dan Pengembangan Kependidikan, 2026)
Basic education confronts globalization and Industry 4.0 challenges demanding enhanced teacher professionalism, yet public elementary schools in Tunjung Teja District exhibit low teacher motivation, commitment, and satisfaction—evidenced by 30% tardiness, 87.5% lacking extra teaching initiative, and facility/benefit complaints. This study investigates transformational leadership (Bass & Avolio) effects on teacher performance (Permendiknas No. 16/2007) mediated by organizational commitment (Meyer & Allen) and job satisfaction (Herzberg). Employing a causal explanatory quantitative design via cross-sectional survey of 40 teachers (simple random sampling), self-reported Likert-scale questionnaires assessed all variables, showing strong validity (r=0.73-0.78) and reliability (α=0.83-0.86). Results revealed very high leadership (4.38), high commitment/satisfaction (4.07 each), and very high performance (4.12); significant regression (R²=0.68, F=18.45, p<0.001), strong leadership prediction (β=0.52, p<0.001), and mediation (Sobel p<0.05) supported all hypotheses. Transformational leadership effectively boosts performance via commitment and satisfaction; recommendations urge principal training and intrinsic satisfaction enhancements for education quality.